THE CONCEPT OF PEACE AND HARMONY IN THE SCRIPTURES OF HINDU RELIGION AND PHILOSOPHY THROUGH THE AGES IN INDIA - Subhra Sabhapandit (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Indian culture is a treasure house of different philosophical & religious sects. Following different faiths, the Indians have been living together with peace and harmony for around three thousand years. Though there were philosophical dissentions & religious conflicts, these seldom escalated into a large scale pogroms or massacres of innocent lives. The paper is a modest endeavour to highlight those foundations, which have always established peace and harmony among various philosophical and religious sects.